Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

X-ray photoelectron spectroscopic investigations of Cu2O nanoparticles - Nikesh, V. V.; Mandale, A. B.; Patil, K. R.; Mahamuni, Shailaja (Materials Research Bulletin, 2005)
Cuprous oxide nanoparticles of five different sizes were obtained by electrochemical as well as chemical routes. Various capping agents were used to passivate the nanoparticles. X-ray diffraction studies show formation of single phased, cubic Cu2O nanoparticles. X-ray photoelectron spectroscopic studies indicate formation of CuO phase on the surface of Cu2O nanoparticles for uncapped as well as for those, capped by tetraoctylammonium bromide. On the other hand polyacrylamide and polyvinyl pyrrolidone capped samples did not show presence of CuO. X-ray photoelectron spectroscopy also indicates formation of a Cu2+ complex with the capping material on the surface of Cu2O nanoparticles. The results were discussed in terms of capability of passivation of various additives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Oxides; photoelectron spectroscopy; Surfaces

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures

Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation